The Role of Elementary Teachers in Visual Arts Instruction: Navigating Challenges in Post-Tsunami Educational Contexts - Anidya Citra Mayuni; Rizal Rizal; Yun Ratna Lagandesa; Andi Nur Isnayanti; Surahman Wilade; Rahmat Maghfirah Ruana (Papanda Publisher, 2026)
This study examines the multidimensional roles teachers perform in Visual Arts instruction for fifth-grade students within the Merdeka Curriculum framework at SD Inpres 1 Talise, a post-disaster educational context in Palu, Indonesia. Employing qualitative descriptive methodology, data were collected through classroom observations, semi-structured teacher interviews, and student questionnaires (n=23) measuring perceptions of teacher effectiveness across 20 items. Results revealed that teachers simultaneously enact three primary roles: educator (20.65% of positive responses), facilitator, and motivator, achieving an overall effectiveness rating of 71.56% despite significant resource constraints. Interview data documented sophisticated pedagogical strategies including character modeling, project-based facilitation, and differentiated motivation techniques. However, persistent challenges emerged including limited facilities, constrained instructional time, and inadequate professional development. Unexpectedly, students demonstrated creative adaptation to resource scarcity through material improvisation and peer mentoring. The findings extend existing literature by demonstrating that moral development remains central to arts education even within student-centered curricula, while revealing how teachers in resource-constrained post-disaster contexts employ adaptive strategies to fulfill complex pedagogical responsibilities. This research contributes empirical evidence for developing targeted teacher professional development, schedule restructuring, and infrastructure investment policies that recognize arts education as critical educational and therapeutic infrastructure, particularly in disaster-affected communities.